PENGEMBANGAN PERANGKAT PENILAIAN BERBASIS KELAS PADA MATA PELAJARAN BIOLOGI SMA KELAS XI - Siti Rukmana; Evi Suryawati; Mariani Natalina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: The purpose of this research is to develop the classroom-based assessment on biology subjects for XI grade Senior high school. Assessment consists of seven graderoom-based assessment techniques. There are paper and pencil test, attitude, performance, product, project, self-assessment and portofolio. The development was conducted at Biology Education University of Riau and the limiting test was conducted at SMAN 8 Pekanbaru. The research held on January until April 2014. Used research and Development (R & D) design with ADDIE model. Subjects consisted of four Basic Competencies (KD) in the XI grade Senior high school. Data were collected by filling the validity of the assessment sheet by each validator which consists of internal and external validators. Collected datas were analyzed by descriptive statistics. Average results of the validity of class-based assessment are: 3.6 for the paper and pencil test, 3.7 for attitude assessment, 3.7 for performance assessment, 3.6 for product assessment, 3.6 for project assessment, 3.8 for self-assessment and 3.7 for portofolio assessment. On the last stage of the research, a limiting test on the XI grade senior high school. Based on the research’s results can be concluded that the development of classroom-based assessment on biology science for XI grade senior high school student was done with the ADDIE model that consists of some phase, start from analyze, design, develop, and the last is implementation in a limiting test. Based on the results of validation, classroom-based assessment could be implemented with the field test.Key words: biology senior high school, classroom-based assessment, development